Genetic nonlinear and random regression models for longitudinal data in order to change the feed intake curve of pigs - Lorenzo Bermejo, Justo (Schriftenreihe des Instituts für Tierzucht und Tierhaltung der Christian-Albrechts-Universität zu Kiel, 2002)
Summary ; Zs.-Fassung
Keywords: Hochschulschrift; Schwein; Tierernährung